2012
DOI: 10.1363/4412512
|View full text |Cite
|
Sign up to set email alerts
|

STD and HIV Risk Factors Among U.S. Young Adults: Variations by Gender, Race, Ethnicity and Sexual Orientation

Abstract: CONTEXT STDs, including HIV, disproportionately affect individuals who have multiple minority identities. Understanding differences in STD risk factors across racial, ethnic and sexual minority groups, as well as genders, is important for tailoring public health interventions. METHODS Data from Waves 3 (2001–2002) and 4 (2007–2008) of the National Longitudinal Study of Adolescent Health were used to develop population-based estimates of STD and HIV risk factors among 11,045 young adults (mean age, 29 at Wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 35 publications
4
55
0
2
Order By: Relevance
“…41 Mojola and Everett used the National Longitudinal Study of Adolescent to Adult Health (Add Health) and showed that it is not uncommon for lesbian young adults to report male sexual partners: on average, white lesbians reported 5.5 male partners, black lesbians reported 8.7 male partners, and Latina lesbians reported 5.0 male partners in their lifetime. 42 While, it is possible that some of these heterosexual sexual relationships were the result of forced sex, in light of recent work that highlights the complexity of women's sexuality, 36,43,44 it is likely that many of these relationships were consensual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Mojola and Everett used the National Longitudinal Study of Adolescent to Adult Health (Add Health) and showed that it is not uncommon for lesbian young adults to report male sexual partners: on average, white lesbians reported 5.5 male partners, black lesbians reported 8.7 male partners, and Latina lesbians reported 5.0 male partners in their lifetime. 42 While, it is possible that some of these heterosexual sexual relationships were the result of forced sex, in light of recent work that highlights the complexity of women's sexuality, 36,43,44 it is likely that many of these relationships were consensual.…”
Section: Introductionmentioning
confidence: 99%
“…46 Including mostly heterosexual and bisexual samples in studies of SMW's experience of unintended pregnancy is important as previous studies have shown that these subgroups report more sexual risk behaviors, including more male partners than either heterosexual or lesbian identified women. 34,42 Such risk factors have been studied primarily in connection with sexually transmitted infections which also increase risk of unintended pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, sexual minority young adults engage in more sexual risk behaviors than do their heterosexual peers. 11,12 Although current reportable disease surveillance systems do not routinely collect data on sexual orientation, previous research suggests that bisexual young adults of both genders are more likely than their heterosexual counterparts to report any STD diagnosis. [12][13][14] Gay and bisexual men, in particular, are at increased risk of having an STD, including chlamydia and gonorrhea; furthermore, HIV-positive men are more likely than others to have these STDs.…”
mentioning
confidence: 99%
“…*  Factor de riesgo de infección por el VIH, sexual, parenteral u otro [43]. *  Tiempo transcurrido entre el inicio de la exposición al VIH y el diagnóstico de la infección por el VIH, en años.…”
Section: B) Variables Clínicasunclassified